Identifying Persian traditional socio-cultural behaviors for application in the design of modern high-rise residences - Abbaszadeh, Shahab; Ibrahim, Rahinah; Baharuddin, Mohd Nasir; Syed Salim, Azizah Salim (ArchNet, 2009)
Our concern is the increasing duplication of Western high-rise residential buildings (HRBs) complexes in metropolises of Iran. By stacking houses, the home has now become mere physical shelter but lacking the socio-cultural meaning that the Persian traditional home has provided. The socio-cultural values of traditional homes that support the households’ life quality by supporting their socio-cultural needs are lost in today’s modern residences. This is a position paper about those missing features with the intent of reinforcing the rich socio-cultural connections and spiritual aspects that are endeared by traditional Persian households in new HRBs complexes. The socio-cultural context in Persian homes emphasizes the behavioral needs at two different social levels: 1) personal space and privacy requirements within the private and semi-private boundary (e.g., family territory of a home), and 2) semi-public and public spaces related to the home environment (e.g., neighborhood communities surrounding the home). Later, the paper discusses the Persian socio-cultural behaviors in contemporary neighborhood communities in HRBs complexes. It concludes with recommendations for future studies to support the development of strong neighborhood communities in non-Western metropolises in contemporary society.